1994
DOI: 10.1021/ja00096a011
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Interactions of Methylene Blue with Polynucleotides and DNA: A Spectroscopic Study

Abstract: The modes of binding of the phenothiazinium dye methylene blue (1) to alternating and nonalternating polynucleotides and to calf thymus (CT) DNA have been characterized using linear dichroism (LD) and circular dichroism (CD) spectroscopy. With the polynucleotide [poly(dG-dC)]2 the interaction at low binding ratios is shown to be purely intercalative and the binding mode is insensitive to changes in ionic strength. The observed CD spectrum is bisignate, which may be due to intercalation at the different base-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
198
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 0 publications
26
198
0
1
Order By: Relevance
“…The methylene blue curve could be fitted with a bi-exponential function, the first z, resembling that without ligand and the second one significantly longer, although it represented only a small amplitude of the decay. This behaviour may be rationalized in terms of methylene blue having two binding modes and at the ME'' concentration employed in these experiments [44], some of the ligand may be bound in the major groove (short 7 , ) and the rest intercalated (long T.,).…”
Section: Effectmentioning
confidence: 81%
See 1 more Smart Citation
“…The methylene blue curve could be fitted with a bi-exponential function, the first z, resembling that without ligand and the second one significantly longer, although it represented only a small amplitude of the decay. This behaviour may be rationalized in terms of methylene blue having two binding modes and at the ME'' concentration employed in these experiments [44], some of the ligand may be bound in the major groove (short 7 , ) and the rest intercalated (long T.,).…”
Section: Effectmentioning
confidence: 81%
“…We also estimate from the simple Scatchard equation the amount of ligand expected to be bound in the experiments [43], assuming for all ligands except distamycin A that all the DNA base pairs represent potential binding sites. Under low-ionic-strength conditions, methylene blue binds to heterogeneous DNA by intercalation but as the ionic strength is raised it tends to change binding mode to external (probably major groove) binding in A+T-rich regions [37, 44,451. The binding constant given in Table 1 is for average binding in any mode and we use this to calculate DNA occupancy assuming all sites are available.…”
Section: Methodsmentioning
confidence: 99%
“…10,11,14,[19][20][21] Due to the aforementioned difficulties, some reports do not agree on the orientation of the basepairing plane of dsDNA, assessed using LD r spectroscopy in the UV, where nucleic acids strongly absorb. Inclination angles of up to 25 • have been reported, 11,14,19,20 whereas structural studies reported the base-pairing plane to make only a small (<10 • ) angle with respect to the B-form helix.…”
Section: Introductionmentioning
confidence: 99%
“…14,22,23 A similar disagreement exists about the orientation of fluorescent dyes intercalated in dsDNA. 10,11,14,[20][21][22][23][24] In addition to spectrometric assays, polarized fluorescence microscopy has been applied to the study of intercalated dye orientation. [25][26][27][28] In these cases, samples were oriented using hydrodynamic flow.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of isosbestic point at a wavelength λ = 377 nm and at C ligand / C DNA ≤ 2.0 indicates that there is no considerable amount of free ligand in the system. Changes in the intensity and spectrum shift occur due to the transition of monomeric binding type to dimeric one [12,13]. Isobestic point at λ = 413 nm corresponds to the band of spectra which comprises spectrum of free ligand and complexes at C ligand / C DNA ≤ 2.0, and characterizes the equilibrium between free ligand and dimeric bound.…”
Section: Spectrophotometric Titrationmentioning
confidence: 99%